Efficient Inhibition of SARS‐CoV‐2 Using Chimeric Antisense Oligonucleotides through RNase L Activation. Issue 40 (18th August 2021) - Su, Xiaoxuan; Ma, Wenxiao; Feng, Di; Cheng, Boyang; Wang, Qian; Guo, Zefeng; Zhou, Demin; Tang, Xinjing
Abstract: There is an urgent need to develop antiviral drugs and alleviate the current COVID‐19 pandemic. Herein we report the design and construction of chimeric oligonucleotides comprising a 2′‐OMe‐modified antisense oligonucleotide and a 5′‐phosphorylated 2′‐5′ poly(A)4 (4A2‐5 ) to degrade envelope and spike RNAs of SARS‐CoV‐2. The oligonucleotide was used for searching and recognizing target viral RNA sequence, and the conjugated 4A2‐5 was used for guided RNase L activation to sequence‐specifically degrade viral RNAs. Since RNase L can potently cleave single‐stranded RNA during innate antiviral response, degradation efficiencies with these chimeras were twice as much as those with only antisense oligonucleotides for both SARS‐CoV‐2 RNA targets. In pseudovirus infection models, chimera‐S4 achieved potent and broad‐spectrum inhibition of SARS‐CoV‐2 and its N501Y and/or Δ H 69/Δ V 70 mutants, indicating a promising antiviral agent based on the nucleic acid‐hydrolysis targeting chimera (NATAC) strategy. Abstract : Based on the strategy of nucleic acid hydrolysis targeting chimera, 5′‐phosphorylated 2′‐5′‐poly(A)4 ‐modified chimeric oligonucleotides were developed for enhanced degradation of the envelope or spike RNA of SARS‐CoV‐2 in vitro. The oligonucleotides can recognize specific viral RNA sequences and 2′‐5′ poly(A)4 can activate RNase L to cleave them specifically.